Non-communicable diseases in pregnancy in Uganda: a growing threat to maternal and neonatal outcomes - Herbert, Luswata; Elioba, John L. R.; A. Muse, Fatima; D. Warsame, Fardowso; Emmanuel, Okurut (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
In Uganda, the number of non-communicable diseases (NCDs) that contribute to poor maternal and newborn outcomes is rising. These diseases include hypertension, diabetes mellitus, cardiovascular diseases, asthma and thyroid disorders. The burden of non-communicable diseases (NCDs) among pregnant women is increasing due to increased urbanization, changes in lifestyle and constraints in the health system. The epidemiology, pathophysiology, screening methods and accepted practices of the common NCDs affecting pregnant women in Uganda are examined in this review. The report also highlights significant shortcomings in the health system and contrasts national recommendations with international standard.